Princing on Dual Channel Supply Chain by Considering Flash Sale Program on Online Channel (Case Study: A3 Printing) - Achmad Amir; Suparno Suparno (Institut Teknologi Sepuluh Nopember, 2020)
Dual channel supply chain is a combination of offline channel and online channel are running simultaneously as a new structure. Through online channels, consumers can find the best product prices. This is used by companies to implementing promotional prices to attract the attention of online consumers, one of them is by the flash sale program. Promotion aims to stimulate demand for a company’s product but along with the increase in demand is not always accompanied by an increase in profit. So it is necessary to consider the selling price of the product during the promotion and how long the promotion will be applied. This research is focused on determining the selling price of products and duration of the promotion as well as the impact using the help of Malpe software and Microsoft Excel. This study concluded that the lower price and the longer duration applied during the flash sale leads on the higher demand but will result in a decrease in profits. So that promotional strategies using the flash sale program can be applied if the company's main goal is only to increase the number of sales.